Oxidative stability of biodiesel in the presence of leaves and fruit extracts - Branco, Isadora Guilherme; Romagnoli, Erica Signori; Gonçales Filho, José; Mantovani, Ana Carolina Gomes; Borsato, Dionisio (Ciência agronômica, 2025)
ABSTRACT This research evaluated the efficiency of ethanolic extracts from yerba mate leaves (Ilex paraguariensis), coffee leaves (coffea arabica), and jambolan pulp (Syzygium cumini Lamarck) through the application of the simplex-centroid mixture design, the super modified simplex optimization algorithm, and the functions of desirability, using the induction period (IP) and the rate constant (k) of the biodiesel oxidation reaction at 110 °C as responses. Antioxidant activity was observed in all extracts, manifesting either by reducing the rate constant or extending the biodiesel induction period in comparison to the control sample. The mathematical models derived from the simplex-centroid design exhibited adjusted determination coefficients of 0.990 for the IP model and 0.960 for the k model. Analysis of variance indicated the significance of both models at the 5% significance level for IP and k, with p1 = 7.382 × 10−4 and p2 = 1.177 × 10−3, respectively. The lack of fit was not significant at the same level with p1 = 0.132 and p2 = 0.653, showing that they can be used for predictive purposes. The analysis of the response surface and optimization using the super modified simplex method revealed that higher proportions of coffee leaves extract in the mixture yielded superior IP values and lower k values.